The Effect of Profitability, Leverage, Liquidity, and Green Accounting on Corporate Social Responsibility Disclosures: Study on Mining Companies Listed on the Indonesia Stock Exchange from 2016 to 2020 - Laksmi, Ayu Chairina; Hanin, Imtiyas Ula Dhiya (Jurnal Aplikasi Bisnis, 2022)
A company will maintain their existence and build a favorable image in public's eyes by fulfilling their social and environmental responsibilities as consequences of their expanding business. The Indonesian government through Law No. 32 of 2009 asserts the importance of balancing natural resource management, utilization of natural resources and human interests. However, there are still violations in the utilization of Indonesia's natural resources, especially in mining companies. This study aims to investigate whether profitability, leverage, liquidity, and green accounting affect Corporate Social Responsibility (CSR) disclosure in mining companies listed in the Indonesia Stock Exchange (IDX) during the period of 2016-2020. This study used quantitative method and secondary data; namely annual reports of mining companies that are listed in the IDX and were analysed using SPSS software program. Multiple linear regression analysis was used to analyse the data. Samples of this study were obtained through purposive sampling technique. The results demonstrate that green accounting have a positive and significant effect on Corporate Social Responsibility Disclosure. Meanwhile, leverage, profitability and liquidity do not show any effects on CSR disclosure.